(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
This article examines the development of corporate governance and the capital structure of large commercial banks with state participation in the Republic of Uzbekistan in the context of ongoing economic reforms. The study focuses on the institutional transformation of joint-stock companies, the strengthening of corporate governance mechanisms, and the gradual reduction of state participation in the economy. Particular attention is given to the financial stability and capitalization of JSCB “Uzbek Industrial and Construction Bank” as one of the major banks operating in the national banking sector. The dynamics of the bank’s authorized capital for the period 2021–2025 are analyzed both in national currency and in US dollar equivalents, taking into account changes in exchange rates. In addition, the structure of shareholders and the level of ownership concentration are examined to assess the influence of institutional investors and the state on corporate governance. The results of the analysis indicate that despite exchange rate fluctuations affecting the dollar equivalent of capital, the nominal level of authorized capital remains stable, confirming the bank’s financial sustainability. The study also highlights the importance of improving corporate governance practices, expanding private sector participation, and strengthening transparency and audit mechanisms in order to enhance investment attractiveness and ensure sustainable development of the banking sector.